Treatment and Outcomes of Metastatic Non-Small-Cell Lung Cancer Harboring Uncommon EGFR Mutations: Are They Different from Those with Common EGFR Mutations? - Jung, Hyun Ae (Biology (Basel), 2020)
SIMPLE SUMMARY: The present study showed the comprehensive analysis of disease characteristics and treatment patterns in uncommon EGFR mutation-positive NSCLC at a major cancer center. This study showed the efficacy of 1G or 2G EGFR-TKIs as the 1L treatment, and subsequent therapy including 3G EGFR-TKIs in the real-world setting. ABSTRACT: Approximately 10% of the epidermal growth factor receptor (EGFR) mutations in non-small-cell lung cancer (NSCLC) are uncommon EGFR mutations. Although the efficacy of second (2G) or third generation (3G) EGFR tyrosine kinase inhibitors (EGFR-TKIs) in the patients with uncommon EGFR mutation has been proven, further studies are warranted to define the optimal treatment approach for uncommon EGFR mutation-positive NSCLC. This study retrospectively investigated the treatment patterns and outcomes of patients with uncommon EGFR mutation-positive NSCLC from January 2011 to December 2019 at the Samsung Medical Center, Seoul, Korea. During the study, 2121 patients with EGFR mutation-positive NSCLC received first-generation (1G, gefitinib or erlotinib) or 2G EGFR-TKI (afatinib) as the first-line (1L) systemic therapy. Of this, 135 (6.4%) patients harbored uncommon EGFR mutations. Of 135, 54 (40%, 54/135) patients had overlapping mutations with major EGFR mutations. The objective response rate (ORR) for the 1L EGFR-TKI was 63.3%. The median progression-free survivals (PFSs) were 8.6 months (95% CI: 3.8–13.5), 11.7 months (95% CI: 6.6–16.7), 7.7 months (95% CI: 4.9–17.4), and 5.0 months (95% CI: 3.7–6.1) for major uncommon EGFR mutation (G719X, L861Q), compound mutation with major EGFR mutation (Del 19 or EGFR exon 21 p.L858R), other compound mutation, and other uncommon mutations, respectively. The median overall survivals (OSs) were 25.6 months (16.9–34.2), 28.8 (95% CI: 24.4–33.4), 13.5 months (95% CI: 7.4–27.8), and 9.4 months (95% CI: 3.4–10.5) for major uncommon EGFR mutation (G719X), compound mutation with major EGFR mutation (Del 19 or EGFR exon 21 p.L858R), other compound mutation, and other uncommon mutations, respectively. The response rate, median PFS, and OS were 63.3%, 16.3 months (95% CI: 15.6–16.9), and 37.5 months (95% CI: 35.4–39.6) for common EGFR mutation-positive NSCLC. After failing 1L EGFR-TKI, repeated tissue or liquid biopsy were carried out on 44.9% (35/78) of patients with T790M detected in 10/35 (28.6%) patients. With subsequent 3G EGFR-TKI after failing the first-line EGFR-TKI, the ORR and PFS for 3G EGFR-TKI were 80% and 8.9 months (95% CI: 8.0–9.8). These patients showed a median OS of 34.6 months (95% CI: 29.8–39.4). The ORR, PFS and OS were poorer in patients with uncommon (especially other compound and other uncommon mutation) than those with common EGFR mutations. T790M was detected in 28.6% of the uncommon EGFR mutation-positive patients for whom prior 1G/2G EGFR-TKIs failed and underwent repeat biopsy at the time of progression.